THE CONTRADICTIONS OF THE MILITARY NEUTRALITY AND THE PRINCIPLE OF DETERRENCE: THE CASE OF SERBIA - Jovanović, Miloš (National interest, 2025)
The present paper raises the question of whether Serbia's military neutrality constitutes an obstacle to its principle of deterrence or, on the contrary, it contributes to its strengthening. After explaining the notions of both deterrence and military neutrality, the answer given by the author is that military neutrality represents prima facie a significant impediment in terms of deterrence since it makes impossible, by definition, any membership to a military alliance, which means one classical mode of deterrence. Furthermore, as military neutrality does not correspond to the concept of neutrality and its legal regime, it cannot be identified with this second mode of deterrence. On the other hand, and this is the paper's main finding, the military neutrality of Serbia accentuates all the immaterial elements of power, such as national spirit, character, or morale, and, therefore, paradoxically reinforces the principle of deterrence.
Keywords: deterrence; military neutrality; Serbia; military alliances; strategic environment; foreign policy